“Efecto comparativo de cinco bioestimulantes comerciales en el rendimiento del tomate (lycopersicon esculentum L. mill) variedad rio grande en el bajo mayo” - Carbajal Sangama, Terwin (2001)
With the main object of knowing that way the bio stimulating increases the yield and the quality of the tomato, the decided to cany out the denominated investigation work: comparative Effect of five commercial bio stimulating in the yield of the tomato (Lycopersicon esculentum. L. MILL) Big River Variety, comparing with a Witness. The present rehearsal was carried out in a floor that has the following ones characteristic: texture sandy franc, pH = 7,12 (lightly alkaline), half organic matter (3,55%), I lower in nitrogen (8,0 half ppm) y in match (27,0 ppm) and interchangeable potassium (0,46 meq/lOOgr.), located in the I found OASIS, district ofMorales, County and Region San Martín. The design ofblocks was used totally at random (DBCA) with four repetitions and six treatments. The seeding of the tomato in went grin house to continuous jet with a distancing of 1 O cm among lines and using of 8 seed g for square meter. In definitive field you employment a distancing of 0,80 meters between furrow or line and 0,50 meters among plants making a populational density of 25 000 plants for hectare. The results demonstrate that the biggest yield was obtained with the treatment T2 (I Excite) with 39,20 t/ha and it turned out to be the economic but (I Benefit - Cost = S /. 3.41) in comparison with the witness that occupied the last place in yield. The economic analysis also demonstrates us that all the treatments overcame the production costs.